Thompson R. Buchanan papers - Buchanan, Thompson R.
Survey concerning federal aid for the arts, originally written in 1961 and recreated in 2000 by Buchanan, together with replies (1961) from Robert Woodruff Anderson, George Balanchine, Norman Mailer, and Herman Wouk.
Federal government employee.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Anderson, Robert, -- 1917-2009 -- Correspondence; Balanchine, George -- Correspondence; Mailer, Norman -- Correspondence; Wouk, Herman, -- 1915- -- Correspondence; Federal aid to the arts -- United States; Government employees